Compelling conversations : questions and quotations on timeless topics : (Chimayo Press, 2008)
This innovative English as a second language textbook helps advanced English language learners develop conversation skills and improve fluency by sharing experiences, reflecting on their lives, and discussing proverbs and quotations. The ESL book includes 45 thematic chapters, over 1400 questions, 500 vocabulary words, 250 proverbs and American idioms, and 500 quotations. Designed for both adult education and intensive English language students, the conversations deepen critical thinking skills and speaking skills essential to success in community college and university programs. Compelling Conversations has been used in classrooms in over 50 countries, recommended by English Teaching Professional magazine, and enjoyed by thousands of English students.